2014
DOI: 10.15341/jmer(2155-7993)/06.04.2014/006
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Professional Development on ICT Use: A Saudi Sustainable Development Model

Abstract: Teachers are the key knowledge producers and the development driving force of any nation. Studies have shown that, the wealth of any nation largely rests on empowering its knowledge producers and knowledge generators. Training teachers on necessary skills and knowledge for personal and career development is a must for attaining sustainable societal development. One of the Saudi's Ninth Development Plan is to turn the Saudi society into information society through various mechanisms notably training and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…According to Al‐Madani and Allaafiajiy () study, the Saudi government recognizes that the quality of its people should be first advanced to sustain its economical growth. Within this purpose, the Saudi government designs three sustainable development programs in education starting from 2004: Watani Project, Tatweer Public Education Program, and Jehazi Project (Al‐Madani & Allaafiajiy, ). The common purpose of all three projects held was teachers’ development in technology competence and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…According to Al‐Madani and Allaafiajiy () study, the Saudi government recognizes that the quality of its people should be first advanced to sustain its economical growth. Within this purpose, the Saudi government designs three sustainable development programs in education starting from 2004: Watani Project, Tatweer Public Education Program, and Jehazi Project (Al‐Madani & Allaafiajiy, ). The common purpose of all three projects held was teachers’ development in technology competence and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…A further review of extant studies posits that ICT-based professional development enables teachers to effectively use ICT in their classroom practices, and supports their classroom pedagogical needs in different contexts, based on their differences in learning and interactions with learners (Al-Madani & Allafiajiy, 2014). In a study conducted by Ajani (2021Ajani ( , 2022, findings revealed that despite teachers' different ways of learning; the TPACK allows teachers to learn meaningfully and interact with others, using various learning resources; providing support through monitoring and feedback to improve their classroom pedagogy (González-Sanmamed, Sangrà, & Muñoz-Carril, 2017).…”
Section: Teacher Professional Developmentmentioning
confidence: 99%
“…Taking the opinions of a random sample of academic staff in Saudi Arabia institutes for this survey, we suggest to more develop the vision to the effectiveness utilizing of ICT resources and ICT capabilities because of a huge developing area of future technology and the uses in all fields. We mentioned earlier that there exists a gap in using ICT in classroom and there is a shortage in training to academic staff (Ageel, 2011;Al Mulhim, E., 2014;Al-Madani & Allaafiajiy, 2014). Others suggest that Saudi Arabian universities must improve their ICT infrastructure, including the provision of suitable connection networks and formal training of staff in utilizing ICT resources (Alturise et al, 2016).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%